REPOSITION OF PESANTRENT KIYAI IN POLITICAL DYNAMICS - Rahiman Dani; Qolbi Khoiri (International Journal of Southeast Asia, 2021)
This paper aims to reveal and explain the dynamics of Islamic boarding school kiyai in relation to national politics and review the repositioning of the role of the kyai in the dynamics of national politics. Although there have been many analyzes regardingthe role of the kyai, the fact is that the ups and downs of the pesantren's kiyai position are increasingly visible. This can be proven by the practical involvement of the kyai in politics so that it has an impact on the existence of the pesantren education institutions that they manage. The results of the author's analysis illustrate that it is time for the kiyai to return to their central role as the main figure in the management of pesantren, this is important to do so that the existence of pesantren inthe modern era is maintained and focuses on reformulation of the bastion of morals and morals of the ummah which is increasingly worrying. The reformulation that the author offers is through the internalization and adaptation of modern civilization for kyai and focuses on improvements in educational institutions, both in the fields of economy, socio-culture, and technology.